Digital Marketing Strategy and Consumer Purchase Intention: A Literature Review on E-Commerce Business Research - Ezra Reni Silva Situmorang; Daniel Pangaribuan; Riris Hutapea; Michael P.J. Silaban (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2025)
The rapid growth of e-commerce has transformed the business landscape and consumer purchasing behavior in the digital economy. Advances in internet technology, increasing smartphone penetration, and the widespread use of online platforms have encouraged businesses to adopt digital marketing strategies to enhance market reach and competitiveness. This study aims to analyze the role of digital marketing strategies in influencing consumer purchase intention in e-commerce businesses through a literature review approach. The study uses a qualitative research method by reviewing and synthesizing relevant scholarly articles published between 2020 and 2024 obtained from reputable academic databases. The analysis focuses on key digital marketing strategies, including social media marketing, influencer marketing, content marketing, search engine marketing, and electronic word-of-mouth, and examines how these strategies influence consumer behavior in online shopping environments. The findings indicate that digital marketing strategies significantly contribute to increasing brand visibility, customer engagement, and consumer purchase intention. In addition, several mediating factors such as trust, brand image, perceived usefulness, and information quality strengthen the relationship between digital marketing practices and consumer purchase decisions. The study also highlights the growing importance of data-driven marketing and personalized digital communication in improving marketing effectiveness in e-commerce platforms. Overall, the results suggest that businesses must adopt integrated digital marketing strategies to remain competitive in the rapidly evolving digital marketplace. This study contributes to the existing literature by providing a comprehensive synthesis of recent research on digital marketing and consumer purchase intention in e-commerce contexts.